Retinal tissue thickness in type 1 and type 2 diabetes. (January 2016) - Srinivasan, Sangeetha; Pritchard, Nicola; Sampson, Geoff P; Edwards, Katie; Vagenas, Dimitrios; Russell, Anthony W; Malik, Rayaz A; Efron, Nathan
Abstract : Background: The objective was to investigate full retinal and inner retinal thickness in individuals with type 1 and type 2 diabetes. Methods: Eighty‐four individuals with type 1 diabetes (T1DM), 67 individuals with type 2 diabetes (T2DM) and 42 non‐diabetic individuals (control group) were enrolled. Participants underwent full retinal thickness evaluation in the central retinal, parafoveal and perifoveal zones and in the retinal nerve fibre layer (RNFL) and ganglion cell complex (GCC), using spectral domain optical coherence tomography. As a preliminary step, the key variables of interest – age, sex, diabetic retinopathy (DR), duration of diabetes and HbA1c levels – were analysed and compared between the three groups. Full retinal thickness, RNFL and GCC thicknesses were also compared between the groups. The relationship between the type of diabetes and retinal tissue thickness was explored, adjusting for the five potential confounders. Results: Compared to individuals with T1DM, individuals with T2DM had significantly reduced full retinal thickness in the parafovea and perifovea and reduced RNFL and GCC thickness. The mean differences were six (p = 0.020), seven (p = 0.008), six (p = 0.021) and four micrometres (p = 0.013) for the parafovea, perifovea, RNFL and GCC thicknesses, respectively. Thicknesses within the central zone (p = 0.018) and at the parafovea (p = 0.007) were significantly reduced in T2DM when compared to the control group. After adjusting for age, sex, diabetic retinopathy, duration of diabetes and HbA1c levels, the relationship between type of diabetes and retinal tissue thickness was not statistically significant (p > 0.056). Conclusion: Retinal tissue thickness is not significantly different between type 1 and type 2 diabetes, when adjusted for age, sex, diabetic retinopathy, duration of diabetes and HbA1c levels.